‘The Hermit Next Door’: The Role of Eremitism/Asceticism in Contemporary Shamanic Healing Practices in North-East Scotland - Barmpalexis, Athanasios (Český lid, 2021)
Based on an ethnographic study of ‘Western’ forms of contemporary shamanism in North East Scotland, the article discusses the significant role that eremitism plays in folk healing systems, particularly in shamanism. The tendency to live an isolated life is not only a key feature of traditional shamanic healing practices, but it can also be found in contemporary manifestations of them. Two such cases are discussed in this article. Terry Mace and Norman Duncan are two contemporary shamanic healers who live and offer services in the wider region of North East Scotland. For different individual reasons, they have self-consciously decided to isolate themselves geographically, living simply and self-abundantly, and leading an eremitic way of life away from materialism and socialising. The article thus focuses on examining the role of eremitism in the life of these two healers in an attempt to highlight the significance of the phenomenon in contemporary shamanisms.